The Influence of Transactional Leadership, Communication, and Workload on Job Satisfaction which Impacts Turnover Intention (Study on Mekaar Account Officers at PT Permodalan Nasional Madani, Kendari Branch) - Moeldayanti, Dian; Noerman, Teuku (PT FORMOSA CENDEKIA GLOBAL, 2024)
The problem of employee turnover is very important and must be identified so that companies can reduce turnover rates and minimize the impacts caused by turnover itself. The purpose of this study was to analyze how transactional leadership style, communication, and workload impact employee job satisfaction which causes turnover intention of Mekaar employees in the Kendari Branch. The research method was carried out quantitatively using the survey method. Through a questionnaire, data was obtained which was distributed to 151 Account Officers of Mekaar, Kendari Branch. The non-probability sampling method was used to select respondents. SmartPLS software was used in this study to analyze data using the SEM (Structural Equation Modeling) method. The results of this study were to determine the results of the analysis of the direct and indirect influences. While the job satisfaction variable on turnover intention had a positive and insignificant impact. The indirect influence through job satisfaction on transactional leadership and communication variables had a positive and insignificant effect, but the workload variable on turnover intention mediated by job satisfaction had a negative and insignificant effect